PROMOSI PAKET WISATA PADA PT. EKSIS TOUR AND TRAVEL PEKANBARU - Baihaqi, Gilang; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Tourism as an important sector in the economy faces the challenges of digital competition and changes in consumer behavior, so tour package promotions are key to attracting and retaining customers, especially at PT. Eksis Tour and Travel Pekanbaru. This study uses a qualitative descriptive approach to examine the effectiveness of promotional strategies including advertising, sales promotions, personal selling, public relations, and direct selling through interviews and direct observations at the PT. Eksis Tour And Travel Pekanbaru office. The results show that these strategies increase customer engagement and sales, despite constraints such as limited resources and lack of promotional innovation. Personal communication and strategic partnerships have proven effective in building loyalty and expanding the market. Therefore, diversifying promotional strategies, staff training, strendgthening partnerships, and utilizing data analysis are essential to optimize marketing and strendgthen the company's competitive position in the dynamic tourism industry. Keywords: Tourism, Promotion, Tour Packages, PT. Eksis Tour And Travel